Pengaruh Jus Semangka Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Diabetes Melitus Di Rw Xiv Kelurahan Surau Gadang Wilayah Kerja Puskesmas Nanggalo Padang - Novita, Yulia Adha (Initium Medica Journal, 2021)
Diabetes Melitus a real public health problem. In general, 50% of people with diabetes has been accompanied kompliksi when diagnosed diabetes mellitus. Handling nonfarmakologik one with complementary therapies. Complementary-alternative treatment is more appropriate for metabolic and degenerative diseases, use a long time, but its side effects are relatively small when used appropriately so that it can become the people’s choice to address blood sugar. The purpose of this study was to find out. Effect of decoction of leaves Regards To Decrease Blood Glucose In Type II Diabetes Mellitus Patients in Puskesmas Padang Lubuk Buaya 2015. Type of quasi experimental research design with one group pretest posttest. The population was patients with Hipertensi in Puskesmas Padang Lubuk Buaya as much as 134 people to sample 15 people .. Mechanical sampling non probability sampling. Then analyzed using univariate descriptive statistics such as percentages and bivariate frequency distribution using T test with a degree of confidence α = 0.05. The results showed that the average blood glucose levels prior to administration 243.6 stew bay leaves. An average of 183.2 in blood glucose levels after administration of a decoction made of bay leaves. There is the influence of decoction of leaves against a decrease in blood glucose levels in patients with Hipertensi in Puskesmas Padang Lubuk Buaya 2015. Expected health workers can provide information through interviews and using leafleat along with a poster that in addition to pharmacological drugs, non-pharmacological drugs may also lower blood glucose levels. In particular the provision of bay leaf decoction is proven to lower blood glucose levels.